Bonifacio ang unang pangulo - Padilla, Robin; Morales, Vina; Padilla, Daniel; Williams, Enzo; TBA Studios (Firm). ([Place of production not identified] TBA Studios, 2014)
"The true story of Andres Bonifacio, a man who rose as a leader in the fight against the Spanish oppressors, and would gain the enmity of even those fighting for the same cause."
Summary taken from: https://www.imdb.com/title/tt4304364/?ref_=fn_al_tt_1
Produced by Rina Navarro, music by Von De Guzman; cinematography by Carlo Mendoza.
Robin Padilla, Vina Morales, Daniel Padilla.
DVD
In Tagalog
Keywords: Drama; History